(untitled) - Luenberger, David G; Ye, Yinyu (NY., 2016)
Introduction.- Part I: Linear Programming.- 2. Basic Properties of Linear Programs.- 3. The Simplex Method.- 4. Duality.- 5. Interior-Point Methods.- 6. Transportation and Network Flow Problems.- Part II: Unconstrained Problems.-7. Basic Descent Methods.- 8. Conjugate Direction Methods.- 9. Quasi-Newton Methods.- Part III: Constrained Minimization.- 10. Constrained Minimization Conditions.- 11. Primal Methods.- 12. Penalty and Barrier Methods.- 13. Dual and Cutting Plane Methods.- 14. Primal-Dual Methods.- Appendix A: Mathematical Review.- A.1. Sets.- A.2. Matrix Notation.- A.3. Spaces.- A.4. Eigenvalues and Quadratic Forms.- A.5. Topological Concepts.- A.6. Functions.- Appendix B: Convex Sets.- B.1. Basic Definitions.- B.2. Hyperplanes and Polytopes.- B.3. Separating and Supporting Hyperplanes.- B.4. Extreme Points.- Appendix C: Gaussian Elimination.- Bibliography.- Index.; Includes bibliographical references and index
Keywords: Linear programming; Nonlinear programming; Quy hoạch tuyến tính; Quy hoạch phi tuyến tính